2020
DOI: 10.21273/hortsci14964-20
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Sweetpotato Surface Area and Volume Using a Low-cost 3D Scanner for Identification of Shape Features Related to Processing Product Recovery

Abstract: The growing demand for sweetpotato French fry and other processed products has increased the need for producing storage roots of desired shape profile (i.e., blocky and less tapered). Length-width ratio (LW) is the current de facto standard for characterizing sweetpotato shape. Although LW is sensitive and descriptive of some types of shape variability, this index may be inadequate to measure taper and other subtle shape variations. Prior work has shown that surface area (SA) and volume (VOL) are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
0
10
2
Order By: Relevance
“…Most research investigating size and shape traits of horticultural crops used lab-scale imaging equipment that are slower and cannot be adapted to production scale environments [17,32]. Further, we considered both ideal and deformed sweetpotatoes making our approach capable of quantifying loss due to shape deformation, while many prior studies excluded sub-standard produce [4,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research investigating size and shape traits of horticultural crops used lab-scale imaging equipment that are slower and cannot be adapted to production scale environments [17,32]. Further, we considered both ideal and deformed sweetpotatoes making our approach capable of quantifying loss due to shape deformation, while many prior studies excluded sub-standard produce [4,18].…”
Section: Discussionmentioning
confidence: 99%
“…Previously published methods have focused mostly on 2D morphological features (i.e., height, width, and aspect ratio) and are unsuitable for quantifying produce with highly irregular shapes (e.g., sweetpotatoes, bell peppers, cucumbers, and carrots). In addition, previous studies did not incorporate existing industrial imaging infrastructure, but instead designed or used independent systems for image acquisition, making the methods unsuitable to couple with existing industrial machinery [2,4,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Linking root architecture attributes to storage root formation in sweetpotato paved the way for the systematic investigation of biotic and abiotic variables known to directly or indirectly influence sweetpotato storage root yield potential, including water availability (Villordon et al, 2012a), nitrogen variability (Villordon et al, 2013), virus presence (Villordon and Clark, 2014), and nematode infection (Villordon and Clark, 2018). Regarding sweetpotato in particular, there is increasing interest in understanding the biological and environmental variables that influence primary or main root length because this is directly related to the determination of storage root length and shape (Villordon et al, 2020). Minemba et al (2019) reported evidence of variations in organic exudates among three sweetpotato cultivars in response to Pi levels.…”
mentioning
confidence: 99%
“…Previous studies identified the LW ratio captured from 2D images as the standard feature for quantifying shape variations in agricultural produce [2,33]. However, LW ratio alone is inadequate for capturing sweetpotato shape variation [18]. Our results…”
Section: Discussionmentioning
confidence: 62%
“…13/18 volume as important shape features for horticultural produce [3,18,34,35]. Interestingly, we did not find volume and tail length among the top influencing variables.…”
Section: Discussionmentioning
confidence: 66%